2007
DOI: 10.1091/mbc.e07-03-0270
|View full text |Cite
|
Sign up to set email alerts
|

p21waf1/cip1/sdi1as a Central Regulator of Inducible Smooth Muscle Actin Expression and Differentiation of Cardiac Fibroblasts to Myofibroblasts

Abstract: The phenotypic switch of cardiac fibroblasts (CFs) to myofibroblasts is essential for normal and pathological wound healing. Relative hyperoxic challenge during reoxygenation causes myocardial remodeling. Here, we sought to characterize the novel O(2)-sensitive molecular mechanisms responsible for triggering the differentiation of CFs to myofibroblasts. Exposure of CFs to hyperoxic challenge-induced transcription of smooth muscle actin (SMA) and enhanced the stability of both Acta2 transcript as well as of SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 51 publications
2
35
1
Order By: Relevance
“…Repression of both myofibroblast differentiation and connective tissue biosynthesis by Egr-1 coupled with increased transcription of Egr-1-dependent genes such as interleukin (IL)-1␤, monocyte chemoattractant protein-1, intercellular adhesion molecule-1, macrophage inflammatory protein-2, 10-kDa interferon-inducible protein, and (RANTES) protein may improve wound healing efficiency because these proinflammatory cytokines and chemokines seem to collaborate with hypoxia-induced hypoxiainducible factor ␣ and vascular endothelial growth factor in the repair and expansion of microvascular networks needed to restore blood flow to damaged tissues. We recently reported that hypoxia (3% molecular oxygen) significantly repressed SM␣A gene expression in primary culture preparations of mouse cardiac fibroblasts (Roy et al, 2007). Although the role of Egr-1 in mediating transcriptional response of the SM␣A gene to hypoxia was not specifically examined in that study, we did report a positive correlation between hypoxia, SM␣A gene repression, and elevated levels of YB-1 protein in cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 66%
“…Repression of both myofibroblast differentiation and connective tissue biosynthesis by Egr-1 coupled with increased transcription of Egr-1-dependent genes such as interleukin (IL)-1␤, monocyte chemoattractant protein-1, intercellular adhesion molecule-1, macrophage inflammatory protein-2, 10-kDa interferon-inducible protein, and (RANTES) protein may improve wound healing efficiency because these proinflammatory cytokines and chemokines seem to collaborate with hypoxia-induced hypoxiainducible factor ␣ and vascular endothelial growth factor in the repair and expansion of microvascular networks needed to restore blood flow to damaged tissues. We recently reported that hypoxia (3% molecular oxygen) significantly repressed SM␣A gene expression in primary culture preparations of mouse cardiac fibroblasts (Roy et al, 2007). Although the role of Egr-1 in mediating transcriptional response of the SM␣A gene to hypoxia was not specifically examined in that study, we did report a positive correlation between hypoxia, SM␣A gene repression, and elevated levels of YB-1 protein in cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, we next examined the mRNA expression levels of TRPM2 channels and KCa3.1 in cardiac fibroblasts exposed to hypoxia and normoxia. In addition, we also examined the expression levels of marker mRNAs for myofibroblasts, for example, transforming growth factor (TGF)-β1 (24), cyclin-dependent kinase inhibitor 1 (p21), and α-smooth muscle actin (α-SMA) (25), because hypoxia is known to induce differentiation from fibroblasts to myofibroblasts (6). As illustrated in Fig.…”
Section: Effect Of Hypoxia On Trpm2 Mrna Expression In Rat Cardiac Fimentioning
confidence: 99%
“…Data are expressed as mean -SD (n = 3) *p < 0.05 compared to non-FPP CTL. by real-time polymerase chain reaction assay using SYBR green-I (Applied Biosystems, Carlsbad, CA) as described previously (36,(38)(39)(40). b-Actin was used as the housekeeping gene.…”
Section: Figmentioning
confidence: 99%